Upcycling Underutilized Food Resources: Development of Ready-to-Eat Dehydrated Spicy Papaya (Carica Papaya) Pickle - Santos, Francis Bon; Peñalber, Martina (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study developed and evaluated a Ready-to-Eat Dehydrated Spicy Papaya (Carica papaya) Pickle fortified with Rice-Based Sagip Nutri-Powder as a value-added product for underutilized green papaya. Grounded in food innovation, preservation, nutritional fortification, sensory evaluation, and circular economy principles, the study employed an experimental research design using five formulations (F0–F4) with varying papaya levels and constant proportions of the other ingredients. Seventy-five respondents composed of students, faculty, staff, and untrained Food Technology experts participated in the sensory evaluation using a structured 9-point hedonic scale covering color/appearance, odor/aroma, taste/flavor, chewiness, and general acceptability. Proximate nutritional analysis, shelf-life assessment, Acceptability Consumers Index (ACI), and return on expenses (ROX) analysis were also conducted. Findings showed that increasing papaya content improved nutritional quality by increasing fiber, carbohydrates, energy, and ash content while reducing moisture, which supported better shelf stability. Significant differences were found among formulations in all sensory attributes, with F2 emerging as the most preferred formulation based on general acceptability and ACI. Shelf-life results showed that all formulations remained acceptable for seven days, with F2 demonstrating the greatest stability. Economic analysis revealed that higher papaya content increased production cost and reduced profitability, although F2 provided the most practical balance between acceptability and viability for commercialization. The study concludes that fortified dehydrated papaya pickle is a feasible product for food waste reduction, nutritional enhancement, and livelihood development, and recommends longer shelf-life testing, broader consumer validation, and further formulation refinement. The study is directly connected to SDG 2 (Zero Hunger) through food-based nutritional improvement and SDG 12 (Responsible Consumption and Production) through the upcycling of underutilized papaya and reduction of food waste. It also reflects a sustainability impact by supporting resource-efficient food utilization, improving access to nutrient-enhanced products, and offering potential livelihood and commercialization opportunities for local communities.